Seismic performance quantification of reinforced concrete shear walls with high-strength materials in nuclear facilities: hybrid simulation testing and numerical modelling assessment - Abouyoussef, Mohamed (My University, 2024)
Nuclear facilities use low-aspect-ratio reinforced concrete (RC) shear walls as a primary structural element to resist lateral demands during seismic events. These RC shear walls are commonly designed to have large thicknesses and a few openings to prevent radiation leaks and enhance blast and fire protection. For these reasons, such walls typically have an aspect ratio of less than one coupled with high reinforcement ratios that are provided by two or more mats of large-diameter rebars on both wall faces, leading to complex construction activities and high construction costs. The use of high-strength materials has the potential to enhance the constructability of such walls, by significantly reducing the required steel areas, minimizing material/fabrication costs, and simplifying quality control checks. Despite such advantages, limited studies have been conducted to evaluate the use of high-strength materials in nuclear facilities. In this respect, the current dissertation focuses on addressing this knowledge gap by comprehensively quantifying the seismic response of low-aspect-ratio RC shear walls with high-strength materials, thus facilitating their adoption in future editions of relevant nuclear design standards. Chapter 2 focuses on developing fragility functions for nuclear RC shear walls with high-strength materials at different damage states to evaluate their seismic response compared to their counterparts with normal-strength materials, while also the economic benefits of both material walls are assessed. Specifically, nine low-aspect-ratio RC shear walls are designed to have identical dimensions and similar lateral strength capacities according to relevant nuclear design standards. To perform this evaluation, a numerical OpenSees model is developed and experimentally validated using several walls with a wide range of design parameters and geometrical configurations, tested in previous experimental programs. Incremental dynamic analyses are then performed following the FEMA P695 methodology, and subsequently, fragility functions are developed for the nine walls utilizing the FEMA P58 damage states. Afterward, the total rebar weights and total construction costs of the nine walls are evaluated to quantify the economic benefits of using high-strength materials in nuclear RC construction practice. In previous studies, low-aspect-ratio RC shear walls with high-strength reinforcement (HSR) have been tested under quasi-static fully-reversed cyclic loading to simulate seismic demands. Therefore, Chapters 3 and 4 contain a description of two experimental program phases that utilize the pseudo-dynamic hybrid simulation testing technique to evaluate the performance of nuclear RC shear walls with HSR when subjected to ground motion sequences. Hybrid simulation combines the simplicity of analytical modelling and the efficiency of experimental testing to quantify the response of a complete structural system. In this regard, three RC shear walls with an aspect ratio of 0.83 are subjected to ground motion sequences ranging from operational basis earthquake (OBE) to beyond design basis earthquake (BDBE) levels. Chapter 3 presents Phase I which evaluates the performance of two nuclear RC shear walls with HSR and normal-strength reinforcement (NSR), while Chapter 4 describes Phase II which quantifies the effect of axial loads on two nuclear RC shear walls with HSR. The experimental results of these chapters are discussed in terms of the force-displacement responses, lateral strengths, stiffnesses, effective periods, ductility capacities, cracking patterns, rebar strains, and failure modes. Such experimental results are also used to develop and validate a numerical OpenSees model that simulates the response of nuclear RC shear walls with different axial load levels under ground motion records. The experimental and numerical results are then compared to the current ASCE 41-13 backbone model for RC shear walls. Several past extreme events highlighted the importance of designing and evaluating RC shear walls in safety-related nuclear facilities under multi-hazard scenarios, including post-earthquake fire and accident thermal-seismic scenarios. However, previous studies have focused on the influence of earthquakes following fires on high-aspect-ratio RC shear walls. Also, all studies evaluated their walls under cyclic loading, and therefore, the dynamic response of low-aspect-ratio RC shear walls in nuclear facilities under thermal loading demands followed by different ground motion records has not been investigated. To address this research gap, Chapter 5 presents fragility functions for nuclear RC shear walls under post-earthquake fire and accident thermal-seismic scenarios. To generate such functions, numerical OpenSees models are developed and validated both thermally and mechanically using previous experimental programs that have exposed their RC slabs and shear walls to a wide range of temperature loading demands. The OpenSees models are also verified using two RC shear walls that have been tested under ground motion records at ambient temperatures. The OpenSees models are then used to perform incremental dynamic analyses and subsequently develop fragility functions for low-aspect-ratio RC shear walls under the two multi-hazard scenarios. For the post-earthquake fire scenario, ground motions followed by the ISO 834 standard fire for a three-hour duration are applied to four RC shear walls with different design parameters. For the accident thermal-seismic scenario, three RC shear walls with high elevated temperatures up to 450oF, considering different exposure durations of up to three hours, are subjected to ground motions.